2019
DOI: 10.1111/joor.12812
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between masticatory performance, occlusal contact area, chewing time and cycles, and gastric emptying scintigraphy in dentate subjects

Abstract: Background Good mastication is thought to help digestion in the stomach, hence promoting the health of the gastrointestinal system. However, the correlation between masticatory and gastric function has been controversial. This is partly explained by different food types used to assess the performance of the two organs. Recently, frankfurter sausage has been proposed to be suitable for both masticatory performance and gastric emptying tests. Objectives To examine the relationship between masticatory performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…An extensive clinical examination was conducted to assess occlusal features, and a silicone bite registration material (DMG, O-Bite, Hamburg, Germany) was used to measure occlusal contact areas in the maximum intercuspal position [19]. Full-arch impression was taken by using a silicone impression material (Silagum Putty/Silagum Light, DMG, Hamburg, Germany).…”
Section: Early-stage Preparationmentioning
confidence: 99%
“…An extensive clinical examination was conducted to assess occlusal features, and a silicone bite registration material (DMG, O-Bite, Hamburg, Germany) was used to measure occlusal contact areas in the maximum intercuspal position [19]. Full-arch impression was taken by using a silicone impression material (Silagum Putty/Silagum Light, DMG, Hamburg, Germany).…”
Section: Early-stage Preparationmentioning
confidence: 99%
“…Among those who underwent surgery to improve masticatory function, 85% who initially had abdominal pain reported an improvement after one year. Other studies, however, have found inconsistent results as it relates to the impact of chewing duration and/or efficiency on gastric emptying and GI symptoms (Hattori et al 2008;Koike et al 2013;Kumar et al 2022;Sumonsiri et al 2019). These equivocal findings could be due to differences in participants studied (healthy vs. masticatory dysfunction), nutrient profile of ingested foods, and methods employed to assess gastric emptying.…”
Section: Introductionmentioning
confidence: 99%
“…Masticatory performance is directly correlated with masticatory muscles' work in grinding and cutting food. The measurement of maximum voluntary bite force (MBF) reveals masticatory system activity, and it is correlated with many factors such as dentition status, dental prosthesis and temporomandibular disorders [14]. Many patients adapt their loss of masticatory capability by chewing food for a longer time or using more chewing cycles [15].…”
Section: Introductionmentioning
confidence: 99%